Lesson Ideas of Narrative Reading Comprehension Using Storyboard Makers - Nadrotin Mawaddah; Dwi Fita Heriyawati (VELES Voices of English Language Education Society, 2022)
Even though stories are interesting material to learn, reading them still becomes a difficult skill because students are burdened and bored with piles of words when reading texts. Multimodal text is a solution to this issue that has been widely researched. One example of multimodal texts is the storyboard, which refers to a medium like a comic combining a sequence of storyline pictures and texts such as dialogues and narration. This teaching medium is assumed to have many advantages in improving students’ reading comprehension because students are engaged with the storyboarding activities. Meanwhile, research about how to utilize comics or storyboards in teaching reading comprehension is less well observed. This research aims to investigate the extent of the advantageous lesson ideas in the storyboard makers and the levels of reading comprehension skills that can be taught using the storyboard makers. Since the data is explored and collected from the websites, the design of this study is exploratory research. This study revealed that the two storyboard makers provide a large number of innovative lesson ideas that have been advantageous in teaching narrative reading comprehension. This research also implied that storyboarding can be applied to many levels of reading comprehension skills, including lexical, literal, inferential, applied, critical, and effective comprehension, as well as possibly beneficial for extensive reading.